SINGLE AND SYNERGISTIC EFFECTS OF LYSINE AND PHYTASE SUPPLEMENTATION ON GROWTH PERFORMANCE MEAT QUALITY AND BONE CHARACTERISTICS IN JAPANESE QUAIL (The Research of Medical Science Review, 2025)
Background Objectives Supplementation of both lysine and phytase is important to improve growth performance and carcass yield in poultry birds. The purpose of current study was to evaluate the single and synergistic effect of lysine and phytase on growth performance, visceral organs weight, meat quality, and bone characteristics in Quails birds. Materials and Methods This study was carried out on 240 quails. The duration of trial was 35 days at Avian Research and Training (ART) Centre UVAS, Lahore. The quails were randomly divided into 8 groups and each group comprised of five replicates and each replicate consisted of six birds. Birds were fed with commercial diet (CD) supplemented with lysine sulphate and phytase with ad libitum access of fresh water for 35 days. On day 35, two birds from each replicate (10 birds /group) were selected for sampling. The feed conversion ratio (FCR), alkaline phosphates enzyme activity, gross parameters of visceral organs and various other meat parameters were studied. The data was analyzed with one way ANOVA using SPSS software version 20.0. Results The effects of lysine and phytase supplementation individually and in combination on body weight gain results showed that body weight gain, FCR, feed intake, muscle diameter, bone length, weight and diameter, and meat parameters such as pH, color, and drip loss showed significant difference (P≤0.05) except alkaline phophatase enzyme (P≥0.05). The lysine and phytase supplements showed positive effects on these parameters. Conclusion It was concluded that dietary supplementation lysine and microbial phytase individually and in combination microbial phytase in combination with 8g lysine generally improved meat quality and bone morphometric characteristics in Japanese Quails.